The Impact of FDI on Economic Growth in Southern African Countries - Marandu, Simon Hlomayi (Graduate School of Business (GSB), 2018)
All the countries in southern Africa can be classified as developing, a category which is composed of the world’s poor countries. These countries’ economies are characterized by low Gross Domestic Product (GDP), low levels of employment, and low income levels on the economic front and weak democracies on the political front. However, most of these southern African countries have abundant natural resources which should have given them the means by which to improve their economies. It is generally accepted that the reason why countries in Sub-Saharan Africa (SSA) are in this predicament is because of the lack of capital, skills and technology required to exploit these natural resources and, in some cases, poor political governance and political instability. Multilateral institutions and academia have insisted that for developing countries to accelerate economic growth and social development they should promote foreign direct investment (FDI) in their territories. So in essence the concept of FDI has been proffered as a solution to ignite the much needed economic growth and development (Fischer, 1999). It is envisaged that FDI will provide the missing capital, technology and skills required to exploit the abundant natural resources that countries in southern Africa have. Such activities will then create employment, improve domestic production and in the process increase the level of skills in the developing countries. In general, some literature suggests a positive relationship between FDI and economic development (Kurtishi-Kasrati, 2013). Further, when a country decides to pursue FDI then that country will then be forced by that pursuit to inculcate democratic values and principles and proper governance in its political and administrative systems. The vehicles that bring FDI into the developing countries are varied. The main drivers of FDI are the Multinational Enterprises (MNEs). When investing in countries, the MNE’s objectives are not necessarily aligned with those of the host countries. Most MNEs are inspired by a desire to increase profits, an objective which is usually at odds with the objectives of economic and social development as envisaged by the receiving countries (Bitzenis, 2004). Some studies have shown that FDI can have negative spill-over effects on the domestic economies through repatriation of profits and crowding out of the local industries. Studies have shown that if foreign firms are substantially more advanced technologically than the domestic firms this could result in failure of domestic companies due to loss of market share, generally referred to as ‘market stealing’ (Schoors & van der Tol, 2002). This research seeks to establish whether FDI is having a significant impact on GDP growth in countries in southern Africa. Furthermore, this research will try to look at how other variables enable the economies to absorb and convert the FDI into GDP growth. Some studies have shown that human capital development and financials systems development might facilitate the absorption of FDI in developing economies (Durham, 2004).